The Participation of Parents in School Management: A Perspective of Inclusive Education - Mulyadi, Nandi (International Conference of Moslem Society, 2019)
Abstract This paper is intended to describe the importance of inclusive education, school management that supports inclusive education by mobilizing the participation of parents, and school policies that can accommodate the implementation of inclusive education in schools. To achieve this purpose conducted a literature review and empirical experience is associated with the author. Inclusive education in Indonesia is not negotiable anymore to be implemented systematically, because of Indonesia as the worldâ€™s largest multicultural country, which is more important is that inclusive education is essentially to provide equal education for all children. The implementation of inclusive education in schools can be run effectively and efficiently be supported by effective school management as well. One characteristic of effective school management is the active participation of various stakeholders, including the participation of parents. The participation of parents for their childrenâ€™s education both at home and at school was big contribution to the educational success of children. Similarly, to the success of inclusive education, it needs the active participation of parents. Therefore, schools need a policy that is able to evoke the participation of parents in the context of inclusive education. Some ideas include: school policies that ensure no children are marginalized or even drop out. To that end, the schoolâ€™s policy can be loaded: parental understanding of inclusive education, the services provided parents, parental understanding of school programs, the convenience of parents in participating, as well as contribute more opportunities for older people can afford. One program that can be selected is the â€œfacilitation of child poverty-based parentâ€. Parents who are able socio-economically understand, aware, and willing to support educational facilities for poor children who are effectively coordinated by the school with the school committee. Keywords: parent participation, school management, inclusive education